(untitled) (Jurnal Bahasa, 2022)
This article focuses on research findings of a linguistic process known as comparative method which is carried out in the discipline known as comparative historical linguistics. The expressions of comparative historical linguistics. The expressions of comparative historial linguistics are formed from two terminologies which are historical linguistics and comparative linguistics. The function of historical linguistics is to analyse the development of internal and external elements in languages since the early emergence of that particular languages until a certain point of time whereas, the function of comparative linguistics, involve current dialects or languages that are still exist in the present day. These dialects or languages are used because both are supposedly qist as a result of previous language development. In other words, there is an older form of a language which was thought to disperse "younger" or newer dialects oe languages. Therefore, other than getting a portrayal of the parent language, a specific comparison will be employed to analyse changes that occurred in a dialect or language that was dispersed by the parent language. As a result, the comparative field is supposed to be afield that examines datafrom one or more languages, at least in two periods. The data of one language over two periods or more were compared carefully to obtain changing methods that occurred in that particular language. (Gorys, 1984:22). Using a combination of both comparative and historical linguistic approaches, linguists can make an effort to reach further into the life of the language during the prehistoric period. The efforts can be analysed through four focal points of research in this field. Firstly, this discipline can be used to trace the history of a particular language and to express the relationship between a particular language and other languages during the prehistoric period. Secondly, this discipline also can be used to restore, redevelop or reconstruct the form of the parent language which was thought to disperse the related languages that exist now. Thirdly, this discipline also functions to subgroup or classify languages that is to group languages into specific subgroups based on similar linguistic characteristics and to confirm the related levels between the subgroups of those languages. The fourth focal point of the comparative and historical linguistics is to predict the centres of spread of the parent language and trace the transfer of the parent language speakers from those centres. The pivotal point of this research is on the first focal point that is to trace the history of a particular language and to express relationship of that language with other languages during the prehistoric period. As stated in the comparative and historical linguistics, the relationship between languages can be expressed through the comparative method. For this purpose, the article will compare Lexis of ten Autronesian languages, identify similarities and differences between Lexis of those languages and investigate general processes of change that can be traced from these comparisons.